Obstacles to Skin Self-Examination: Are Frontier Adults Inclined Abstainers? - Jensen, Jakob D. (Psychol Health Med, 2019)
Individuals residing in U.S. frontier counties have limited access to dermatology care and higher melanoma mortality rates. Given these limitations, frontier residents rely disproportionately on skin self-examinations (SSE) for early detection of melanoma, though little is known about their SSE behaviors and barriers to conducting SSEs. The goal of the present study was to identify obstacles to SSE performance via a survey of adults (N = 107) living in a U.S. frontier county. Approximately 43% of participants were classified as inclined abstainers – individuals who intended to perform SSE, but failed to follow through. Compared to those who did follow through, inclined abstainers were more likely to be hindered by twelve barriers, including forgetting, letting other tasks get in the way of SSE, and struggling to identify a good time or routine for SSE performance. The barriers to action for these inclined abstainers are modifiable – for example, not remembering to do it – and well positioned for a behavioral intervention.